The expression, clinical relevance, and prognostic significance of HJURP in cholangiocarcinoma - Yang, Yang; Yuan, Jinyan; Liu, Zhenzhong; Cao, Wenwen; Liu, Pei (Frontiers in Oncology, 2022)
Background Cholangiocarcinoma (CCA) is the malignancy originating from biliary epithelium, including intrahepatic (iCCA), perihilar (pCCA), and distal (dCCA) CCA. The prognosis of CCA is very poor and the biomarkers of different CCA subsets should be investigated separately. Holliday junction recognition protein (HJURP) is a key component pre-nucleosomal complex, which is responsible for mitosis. The ectopic expression of HJURP has been reported in several cancers, but not CCA. Materials and Methods In our study, we investigated the expression of HJURP in 127 CCA patients comprised of 32 iCCAs, 71 pCCAs and 24 dCCAs with immunohistochemistry, and divided these patients into subgroups with low or high expression of HJURP. With chi-square test, univariate and multivariate analyses, we evaluated the clinical correlation and prognostic significance of HJURP in iCCAs, pCCAs and dCCAs. Results HJURP was ectopically up-regulated in CCAs compared with the para-tumor tissues based on the TCGA and other mRNA-seq databases. High expression of HJURP was correlated with low overall survival rates of iCCA and pCCA. Moreover, HJURP was an independent prognostic biomarker in both iCCA and pCCA, but not in dCCA. Patients with high HJURP was more likely to suffer CCA-related death. Conclusions HJURP was an independent prognostic biomarker in both iCCA and pCCA, but not in dCCA. Our results provide more evidence of the molecular features of different CCA subsets, and suggest that patients with high HJURP are high-risk, which can guide more precision follow-up and treatment of CCA.